Analisis Struktur Metode Distribusi Momen (Cross) Menggunakan Microsoft Visual Basic 6.0 - Ardiansyah Ardiansyah; Asri Mulya Setiawan (Universitas Sulawesi Barat, 2018)
The making of the Moment Distribution Method Structure Analysis program using Microsoft Visual Basic 6.0 in this Final Project is intended to introduce Microsoft Visual Basic 6.0 which can be used and applied to create Civil Engineering programs, in this case the compiler for one of them is a program for calculate the Structural Analysis of Moment Distribution Methods. After the Structural Analysis program the Moment Distribution Method is made then the program is tested to determine the accuracy of the desired results. Program testing is done by entering several variations of data input and comparing it with manual calculations. The results obtained are the Structural Analysis Method of Moment Distribution Method using Microsoft Visual Basic 6.0 can be used to calculate structures with multiple load combinations, Momentary Distribution Method Structure Analysis programs using Microsoft Visual Basic 6.0 can still be developed again to create more complicated programs such as continuous rod structures or portal structure.